(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Peptic ulcer is a major health burden that recognized as a group of upper gastro-intestinal tract disorders. The aim of the therapy is to provide relieve from pain and prevent ulcer complications. Therefore, it is essential to evaluate the drug-likeness and toxicity profile of existing drugs for developing new potent anti-ulcer agents. In this research work, we study the pharmacokinetic, toxicity and bioactivity profile of few selected anti-ulcer agents by In silico method. These research investigations provide the lead for the development of new anti-ulcer agents with lesser toxicity and more effectiveness.